Yahoo Answers is shutting down on 4 May 2021 (Eastern Time) and, as of 20 April 2021 (Eastern Time), the Yahoo Answers website will be in read-only mode. **There will be no changes to other Yahoo properties or services, or your Yahoo account.** You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

### 3 Answers

- llafferLv 72 months ago
Not sure why people are disliking a seemingly correct answer. I'll do it with an explanation and see if I get what they get:

8^(1 - x) = 4^(x + 2)

Both 4 and 8 are powers of 2:

(2³)^(1 - x) = (2²)^(x + 2)

The exponent of an exponent is the same as if you took the product of the exponents, so:

2^[3(1 - x)] = 2^[2(x + 2)]

We now have the same value on both sides with the same base on both sides so the exponents must also be the same:

3(1 - x) = 2(x + 2)

Now we can expand both sides and solve:

3 - 3x = 2x + 4

-5x = 1

x = -1/5

I do get the same answer as the others.

- la consoleLv 72 months ago
8^(1 - x) = 4^(x + 2)

[2^(3)]^(1 - x) = [2^(2)]^(x + 2) → you konw that: [x^(a)]^(b) = x^(ab)

2^[3.(1 - x)] = 2^[2.(x + 2)]

3.(1 - x) = 2.(x + 2)

3 - 3x = 2x + 4

- 5x = 1

x = - 1/5

- az_lenderLv 72 months ago
(2^3)^(1-x) = (2^2)^(x+2) =>

2^(3 - 3x) = 2^(2x + 4) =>

3 - 3x = 2x + 4 =>

x = -1/5.